Toxicity response of Poecilia reticulata Peters 1859 (Cyprinodontiformes: Poeciliidae) to some agricultural pesticides - ALIAKBAR HEDAYATI; REZA TARKHANI; AHMAD SHADI (Smujo International, 2012)
Abstract. Hedayati A, Tarkhani R, Shadi A. 2012. Mortality response of Poecilia reticulata Peters 1859 (Cyprinodontiformes: Poeciliidae) to some agricultural pesticides. Nusantara Bioscience 4: 6-10. This research was performed to determine and compare acute toxicity of diazinon and deltamethrin as potential dangerous organic pesticides to assess mortality effects of these chemicals to the freshwater guppy Poecilia reticulata. LC50 of 24 h, 48 h, 72 h, and 96 h was attained by probit analysis by Finney’s and using the maximum-likelihood procedure (SPSS). The 24-96 h LC50 for the diazinon were 40.9±0.98, 33.2±0.84, 23.2±0.74 and 16.8±0.57 ppm respectively. The 24-96 h LC50 for the deltamethrin were 0.297±0.13, 0.236±0.16, 0.204±0.47 and 0.195±0.06 ppm respectively. In the present study, LC50 values indicated that deltamethrin was more toxic than diazinon to this species. LC50 values obtained in the present study were different from the corresponding values that have been published in the literature for other species of fish.